Evaluation of prescription pattern of antibiotics for surgical prophylaxis in secondary care hospital - Joshi, Devesh Kumar; Rizwan, Mohd; Kothiyal, Preeti; Joshi, Yogesh (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Antibiotic prophylaxis is the prevention and in incidence of surgical site infection. This study evaluates the rational use of antibiotics prophylaxis prior to surgery amongst hospitalized patients. Objectives of the study were to investigate the utilization and evaluation pattern of antibiotics for surgical prophylaxis in surgery department. Methods: A prospective observational study was conducted on 100 patients receiving antibiotics in the Department of Surgery of Brijesh Hospital Ramnagar (Nainital) Uttarakhand. Patient undergoing antibiotic prophylaxis treatment were included in the study, exclusion of those patients who had age less than 18, patients with psychiatric disease and those patients not willing to sign on inform consent form. Results: The result observed in 100 patients follow up 8 weeks and evaluate the appropriate use of prophylaxis of antibiotics majority of patients were age group 18-30 years, followed by 41-50 years, 51-60 years, majority were reported in female patients than male, higher utilization of cephalosporins were commonly prescribed due to their relatively lower toxicity and broader spectrum activity and broader coverage of organism for several serious gram negative infection 30 (30%) patients were prescribed penicillin with aminoglycosides, 10 (10%) patients were prescribed with nitroimidazole antibiotics. Conclusions: The overall scenario of antibiotic usage in a Hospital was as per standard recommendations and all the antibiotics used were according to their standard adult and titrated doses and frequencies. In this study we found that Cephalosporines, Penicillins, Aminoglycosides and Nitroimidazole were mostly used classes of drug. Adverse Drug Reactions were minor and well managed.